2017
DOI: 10.1080/2162402x.2017.1387347
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of β-glucan of 200 kDa modulates melanoma microenvironment and suppresses metastatic cancer

Abstract: Converting an immunosuppressive melanoma microenvironment into one that favors the induction of antitumor immunity is indispensable for effective cancer immunotherapy. In the current study we demonstrate that oat-derived β-(1-3)-(1-4)-glucan of 200 kDa molecular size (BG34-200) previously shown to mediate direct interaction with macrophages could alter the immune signature within melanoma microenvironment. Systemic administration of BG34-200 resulted in reversion of tolerant melanoma microenvironment to an imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…By binding to these receptors, β-glucan exerts its immunomodulating effects to defend against infection and prevent tumor growth by activating various immune cells (macrophages, T cells, natural killer cells, etc.) 70 , 71 . Consistent with these studies, we found that solo treatment with β-glucan could indirectly inhibit B16F10 cell growth by skewing macrophages toward an M1 phenotype through activating MAPK and NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…By binding to these receptors, β-glucan exerts its immunomodulating effects to defend against infection and prevent tumor growth by activating various immune cells (macrophages, T cells, natural killer cells, etc.) 70 , 71 . Consistent with these studies, we found that solo treatment with β-glucan could indirectly inhibit B16F10 cell growth by skewing macrophages toward an M1 phenotype through activating MAPK and NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…BG34-induced alteration in TME and LN immune signatures resulted in regression of established primary and metastasis of B16F10 melanoma model in C57BL/6 mice. Such BG34-induced tumor regression was not observed in the CD11b KO mouse model ( 105 ). Results of these studies suggested that soluble BG34 glucans have a great potential to prime immune cells and enable them to mediate innate and adaptive antitumor immune responses.…”
Section: β-Glucan and β-Glucan-based Nanoparticles As Effective Immunmentioning
confidence: 96%
“…β-glucans with different structures appear to stimulate antitumor responses in completely different manners, and these detailed molecular mechanisms need to be further investigated. In vivo administration of oat-derived BG34 glucan could stimulate production of pro-inflammatory cytokines in TME, and the protective immunity was associated with a significant reduction in tumor-infiltrated granulocytes ( 105 ). In contrast, in vivo administration of soluble yeast-derived BG36 glucan did not induce any pro-inflammatory cytokines in TME, and the protective immunity was associated with a significant increase of tumor-infiltrating neutrophils that are primed for CR3-DCC ( 98 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the cell wall of the outer layer of yeast, there are a large number of polysaccharides and proteins, such as β-glucan, chitosan, mannoprotein, and so on [144]. β-glucan, as the most abundant ingredient, can bind to Dectin-1 receptors on immune cells to cause a series of immune responses including phagocytosis [145][146][147]. Cell wall derived from yeast can be utilized as an adjuvant to activate APCs, and next induce immune responses.…”
Section: Fungusmentioning
confidence: 99%